2022
DOI: 10.1002/ange.202203061
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Genetic Code Expansion of a Polyethylene Terephthalate (PET) Hydrolase from the Human Saliva Metagenome for the Degradation and Bio‐Functionalization of PET

Abstract: We report a bioinformatic workflow and subsequent discovery of a new polyethylene terephthalate (PET) hydrolase, which we named MG8, from the human saliva metagenome. MG8 has robust PET plastic degradation activities under different temperature and salinity conditions, outperforming several naturally occurring and engineered hydrolases in degrading PET. Moreover, we genetically encoded 2,3-diaminopropionic acid (DAP) in place of the catalytic serine residue of MG8, thereby converting a PET hydrolase into a cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Most recently, Pfaff et al (2022) constructed L136F/Q138Y mutant of PES-H1 as the best performing variant. Although the importance of the Q138 position in PET hydrolases has no doubt, type I (TfCut2, Cut190 and LCC) and type II (IsPETase, PES-H1) hydrolases (Eiamthong et al 2022) showed different replacement effects. Considering these results, we made several Cut190 variants, as listed in Table 1 and compared their PET hydrolyzing activities (Table 4).…”
Section: Engineering Of Cut190mentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Pfaff et al (2022) constructed L136F/Q138Y mutant of PES-H1 as the best performing variant. Although the importance of the Q138 position in PET hydrolases has no doubt, type I (TfCut2, Cut190 and LCC) and type II (IsPETase, PES-H1) hydrolases (Eiamthong et al 2022) showed different replacement effects. Considering these results, we made several Cut190 variants, as listed in Table 1 and compared their PET hydrolyzing activities (Table 4).…”
Section: Engineering Of Cut190mentioning
confidence: 99%
“…Most recently, a novel PET hydrolase was cloned from a compost metagenome (Sonnendecker et al 2022) and its variant indicated the comparable activity to the LCC variant (Pfaff et al 2022). In addition, PET hydrolases are cloned even from human saliva metagenome (Eiamthong et al 2022). Thermostable mutants of PETase from mesophilic Ideonella sakaiensis (Yoshida et al 2016) have been documented so far.…”
Section: Introductionmentioning
confidence: 99%
“…The Dap-containing PETase can also carry other cargos to functionalize PET as well as other polyester plastics. [42]…”
Section: Labeling and Functionalizationmentioning
confidence: 99%
“…Although PET is particularly resistant to biodegradation, 3,4 a number of naturally occurring PET hydrolases have been reported. [5][6][7][8] Amongst these are cutinases from Fusarium solani, [9][10][11][12] a leaf-branch metagenome (LCC) 6,[13][14][15] and Humicola insolens (HiC) 11,16,17 as well as a hydrolase from Thermobida fusca (TfH). 9,10,18,19 In 2016, the rst known bacterium capable of using PET as its sole carbon source, Ideonella sakaiensis (Is), was discovered.…”
Section: Introductionmentioning
confidence: 99%